Cortical Patterns of Pleasurable Musical Chills Revealed by High-Density EEG - Chabin, Thibault; Gabriel, Damien; Chansophonkul, Tanawat; Michelant, Lisa; Joucla, Coralie; Haffen, Emmanuel; Moulin, Thierry; Comte, Alexandre; Pazart, Lionel (Frontiers in Neuroscience, 2020)
Music has the capacity to elicit strong positive feelings in humans by activating the brain’s reward system. Since group’s emotional dynamics is a central concern of social neurosciences, the study of emotion in natural/ecological conditions gain interest. This study aimed to show that High Density EEG (HD-EEG) is able to reveal patterns of cerebral activities previously identified by fMRI or PET scans when the subject experiences pleasurable musical chills. Participants (11 female, 7 male) were recorded by HD-EEG while listening to their favourite pleasurable chill-inducing musical excerpt; they reported their subjective emotional state from low pleasure up to chills. HD-EEG results showed an increase of theta activity in the prefrontal cortex when arousal and emotional ratings increased, which are associated with orbitofrontal cortex activation localised using source localisation algorithms. In addition, two specific pattern of chills has been identified; a decreased theta activity in the right central region could reflect supplementary motor area (SMA) activation during chills, may be related to rhythmic anticipation processing. A decreased theta activity in the right temporal region may be related to musical appreciation. The alpha frontal/prefrontal asymmetry did not reflect the felt emotional pleasure but the increased arousal (frontal beta/alpha ratio) corresponded to increased emotional ratings. These results correspond with fMRI and PET findings, thus confirming that EEG is a reliable method and a promising tool for the investigation of group musical pleasure through musical reward processing.